Impact of leukoaraiosis severity on the association of time to successful reperfusion with 90-day functional outcome after large vessel occlusion stroke - Mikati, Abdul (Transl Stroke Res, 2019)
INTRODUCTION: The chance for a favorable outcome after mechanical thrombectomy (MT) for large vessel occlusion stroke decreases with the symptom onset-to-reperfusion time (OTR). Patients with severe leukoaraiosis are at increased risk for a poor outcome after MT. However, whether leukoaraiosis modulates to the association between OTR and 90-day functional outcome is uncertain. METHODS: We retrospectively analyzed 144 consecutive patients with successful (TICI ≥2b/3) MT for anterior circulation large vessel occlusion within 24 hours form OTR between January 2012 to November 2016. Leukoaraiosis was dichotomized to absent-to-mild (van Swieten scale score 0–2) versus moderate-to-severe (3–4) as assessed on admission head CT. Multiple linear, logistic, and ordinal regression analyses were used to determine the association between leukoaraiosis, OTR and 90-day modified Rankin Scale (mRS) score, after adjustment for pertinent covariates. RESULTS: Leukoaraiosis was independently associated with OTR on multivariable linear regression (p=0.003). The association between OTR and 90-day outcome depended on the degree of preexisting leukoaraiosis burden as shown by a significant leukoaraiosis-by-OTR interaction on multivariable logistic regression (OR 0.76, 95%-CI 0.58–0.98, p=0.037) and multivariable ordinal regression (OR 0.87, 95%-CI 0.78–0.97, p=0.011). CONCLUSIONS: Pre-existing leukoaraiosis is associated with the 90-day functional outcome after successful reperfusion and impacts the association between the OTR and 90-day mRS among patients undergoing MT. Patients with high leukoaraiosis burden need to present earlier than patients with low leukoaraiosis burden for a similar favorable outcome. Pending confirmation, these results may have important implications for optimizing patient selection for acute stroke therapies.